Risk Values of Weight and Body Mass Index for Chest Wall Thickness in Patients Requiring Needle Thoracostomy Decompression - Chia-Hung Hsu; Tzu-Yin Lin; Ju-Chi Ou; Jiann Ruey Ong; Hon-Ping Ma (Emergency Medicine International)
Introduction. Emergency decompression is needed in patients with tension pneumothorax, a life-threatening condition. The catheter-based needle thoracostomy was suggested using a 5 cm catheter inserted into the 2nd intercostal space (ICS) and 5th ICS according to the ninth and tenth editions of Advanced Trauma Life Support, respectively. A catheter of suitable length may not be available immediately or the muscle structure of the chest wall may be modified in pneumothorax. Furthermore, alternative sites for needle thoracostomy and reference values of chest wall thickness (CWT) should be explored and warranted. Method. CT scan data and medical data of 650 eligible patients from October 2016 to December 2016 were reviewed. CWT values at four ICSs as well as four variables, namely, age, weight, height, and body mass index (BMI) for both men and women were compared using a nonparametric method, namely, the Wilcoxon signed-rank test. The associations between CWT and the four variables were assessed using the Pearson correlation coefficient. The overall performance of BMI, weight, and height in predicting CWT > 5 cm was evaluated using the receiver-operating characteristic (ROC) curve. Finally, the prediction models were built by using the bootstrap method. Results. Four variables, namely, age, height, weight, and BMI, were compared between the men and women groups. All four variables differed significantly between the two groups, and CWTs at all ICSs, except for the 3rd ICS, differed significantly between the two groups. Among the women, the area under the ROC curve (AUROC) of BMI for predicting CWT > 5 cm at 2nd ICS was larger than the AUROC of weight and height. Among the men, the AUROC of weight for predicting CWT > 5 cm at 2nd ICS was larger than that of BMI and height. The reference value tables were provided for five proposed models for women and men, respectively. Under emergencies, the variable, BMI, or even weight itself, could be used for predicting a failure performance of the needle decompression. For women, CWT at 5th ICS was predicted over 5 cm at BMI over 25.9 kg/m2 or weight over 103.1 kg. For men, CWT at 5th ICS was predicted over 5 cm at BMI over 25.5 kg/m2 or weight over 157.4 kg. Conclusion. Needle thoracostomy is the preferred first technique for many emergency providers for decompression. Therefore, a reference table for safe needle thoracostomy decompression at four usual sites, namely, 2nd ICS, 3rd CIS, 4th ICS, and 5th ICS, was recommended, which will enable paramedics and emergency specialists to rapidly determine CWT at the appropriate ICSs during emergencies.